Spatial variation of metal bioaccumulation in the hydrothermal vent mussel Bathymodiolus azoricus - Cosson, Richard P. (2020)
The variability of the bioaccumulation of metals (Ag, Cd, Cu, Fe, Mn and Zn) was extensively studied in the mussel Bathymodiolus azoricus from five hydrothermal vent sites inside three main vent fields of increasing depth along the Mid-Atlantic Ridge: Menez Gwen, Lucky Strike and Rainbow. Metal bioaccumulation varied greatly between vent fields and even between sites inside a vent field with B. azoricus showing a great capacity to accumulate metals. The bioaccumulation of these metals also varied significantly among tissues. The main target was the gills where metals were mainly associated with soluble compounds whereas in the digestive gland they were mainly associated with insoluble compounds. Storage of metals under insoluble forms in B. azoricus seems to be a major pathway for the detoxification of both essential and non-essential metals. Mussels from the studied fields can be discriminated following their metallic load but the segregation relies partially on the composition of the metal-enriched fluids.